Investigating the relationship between efficiency and justice in Islamic economics in comparison with the concept of efficiency in conventional economics - Ali Reza Lashkari (جستارهای اقتصادی, 2019)
The rules and principles that organize society in the use of resources and facilities as well as the distribution of blessings among members of society are among the fundamental issues in the field of social science theories. Efficiency is a symbol of growth and is known as a mechanism for regulating societies' relations. Proponents of social justice in recent decades, reminding the need to pay more attention to it, have proposed justice as the highest criterion for organizing society. These two recent approaches have turned the confrontation between efficiency and justice into one of the central conflicts of economists and the relationship between these two concepts has become a fundamental question. This article examines the relationship between justice and efficiency in the Islamic economic system based on a review of credible sources and documents and using a descriptive-analytical method. This article concludes that efficiency is the most effective use of resources and tools for achieving justice and therefore there is no confrontation between the two concepts.